TI_GERICHTE 11.2004.119 vom 13. März 2006 , Azione di nullità riguardante disposizione a causa di morte: perenzione e litispendenza. - TI Tribunale d'appello (2006)
Azione di nullità riguardante disposizione a causa di morte: perenzione e litispendenza.